2012
DOI: 10.1007/s00428-012-1200-8
|View full text |Cite
|
Sign up to set email alerts
|

Loss of heterozygosity on chromosome 16q suggests malignancy in core needle biopsy specimens of intraductal papillary breast lesions

Abstract: It is often difficult to make a definitive diagnosis of papillary breast lesions using core needle biopsy (CNB) specimens. We studied loss of heterozygosity (LOH) on chromosome 16q in order to assess its diagnostic use for papillary breast lesions in CNB specimens. Of 25 patients with intraductal papillary breast tumors, we extracted DNA from paired samples of tumor cells from CNB specimens and non-tumor cells from subsequent excision specimens and analyzed LOH at the D16S419 and D16S514 loci on chromosome 16q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…A high frequency of loss of heterozygosity (LOH) at chromosome 16p13 and 16q21 was detected both in intraductal papillomas and papillary carcinomas, whereas LOH at locus 16q23 was limited to malignant lesions. LOH at the TP53 locus is also significantly associated with the malignant phenotype . Additionally, a higher PIK3CA or AKT mutation frequency was identified in papillomas than in papillary carcinomas, indicating that papillomas could be driven by mutations in the PIK3CA–AKT pathway, whereas papillary carcinomas might develop along a molecular pathway that is somewhat divergent from that of most benign papillary proliferations …”
Section: The New Adjunct Biomarkers and Genetic Aberrations In Differmentioning
confidence: 99%
“…A high frequency of loss of heterozygosity (LOH) at chromosome 16p13 and 16q21 was detected both in intraductal papillomas and papillary carcinomas, whereas LOH at locus 16q23 was limited to malignant lesions. LOH at the TP53 locus is also significantly associated with the malignant phenotype . Additionally, a higher PIK3CA or AKT mutation frequency was identified in papillomas than in papillary carcinomas, indicating that papillomas could be driven by mutations in the PIK3CA–AKT pathway, whereas papillary carcinomas might develop along a molecular pathway that is somewhat divergent from that of most benign papillary proliferations …”
Section: The New Adjunct Biomarkers and Genetic Aberrations In Differmentioning
confidence: 99%
“…Markers as the CD44 [ 37 ] or cyclin D1 [ 38 ] have been proposed as differentially expressed genes between malignant and benign papillary lesions, but there is no correlation with malignant recurrence of intraductal papillomas. Some genetic alterations, such as loss of heterozygosity of chromosome 16 [ 39 ], have also been proposed as capable of predicting an increased susceptibility for malignant recurrence of intraductal papillomas, but accuracy has not been demonstrated [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…They share some genetic alterations found in low-grade DCIS of other architecture. Studies of papillary breast lesions including invasive papillary carcinomas revealed LOH at loci 16q12.2, 16q21, and 16q23, but LOH at the TP53 locus only in malignant papillary lesions [24,93].…”
Section: Papillary Ductal Carcinoma In Situmentioning
confidence: 99%